The Juridical Analysis of Registration of Business Permits through the Online Single Submission (OSS) System by Notaries - Khaidar, Naufal (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to find out and analyze the registration of business licenses through the online system, Online single submissionsis a new licensing system based on PP No. 5 of 2021 where there is no notary authority in terms of business licensing in accordance with these regulations, but in practice there are many notaries who register business licenses for business actors. This research approach method includes sociological juridical research. Sociological juridical research is legal research using secondary data as initial data, which is then followed by primary data in the field or on the public, examining the effectiveness of a Ministerial Regulation and research that seeks to find relationships (correlations) between various symptoms or variables, as a data collection tool consisting of study of documents or library materials and interviews (questionnaire). The results of the research in this thesis entitled